Development of a novelly selective HPLC-chemiluminescence method by targeting degradation intermediates of nitroimidazoles and its application in animal food products - Mengdie Cai; Xinyu Wang; Kun Lu; Bixiao Zhou; Lijun Wei; Xianglei Cheng (Food Chemistry: X)
Residues of nitro-containing drugs in food and the environment have aroused social concern because of their excessive use for the treatment of human and animal diseases. The disadvantages of complex and time-consuming pretreatments in existing methods make it imperative to develop novel methods. Herein, with the aid of recognition probe MCLA, an excellent selective method for the detection of nitroimidazoles (NDZs) was developed based on high-performance liquid chromatography combined with ultraviolet (UV) degradation and chemiluminescence (HPLC-UV-CL). The study proposed an innovative process for the formation of SO4•−, •OH, and •NO via advanced oxidation processes of NDZs. Six studied NDZs achieved baseline separation within 24 min with detection limits as low as 3 ng/mL (S/N = 3). The proposed method is efficient, cost-effective, and does not require complicated purification steps. This study presents a unique approach for the detection of nitro-containing contaminants and provides new insights into monitoring advanced oxidation processes.